Kepuasan Konsumen dalam Menggunakan Layanan Rumah Sakit Syariah: Peran Komitmen Religiusitas dan Kepatuhan Syariah - Agustina, Nazilatul Farida; Kamal, Al Haq; Sulistiawan, Dedik (Journal of Islamic Economics (JoIE), 2025)
Introduction: The growing demand for Sharia-based healthcare services amid the rapid expansion of the global halal industry has driven Sharia hospitals in Indonesia to continuously improve customer satisfaction. Studies have primarily focused on provider-side determinants such as Sharia compliance, while research integrating both provider factors and internal customer factors such as religious commitment remains limited. This study aimed to analyze the influence of customer’s religious commitment and hospital Sharia compliance on customer satisfaction at Nur Hidayah Hospital, Bantul, Special Region of Yogyakarta. Research Methods: A cross-sectional design was employed with a sample of 100 inpatients. Data were analyzed using multiple linear regression to estimate regression coefficients (b) and 95% confidence intervals. Hypothesis testing was conducted at a 0.05 significance level. Results: Customer’s religious commitment had no significant effect on satisfaction (b = 0.014; 95% CI = -0.189 to 0.217; p = 0.888), indicating that individual religiosity does not directly determine satisfaction with Sharia-based hospital services. In contrast, hospital Sharia compliance had a positive and significant effect on customer satisfaction (b = 0.324; 95% CI = 0.191 to 0.457; p < 0.001). Conclusion: These findings underscore the importance of adhering to Sharia principles in enhancing customer satisfaction. Therefore, improving service quality in alignment with Islamic values should be a priority in the development of Sharia-compliant healthcare systems.